211k views
4 votes
Plz help me !!!!!!!!!!!

Plz help me !!!!!!!!!!!-example-1
User Steven Yue
by
5.0k points

2 Answers

5 votes

Answer:

Explanation:

Only (-3)(-5) = + 15, so the fourth answer is the correct one.

User Savyo Relavio
by
4.9k points
3 votes

Answer:
\bold{d.\ \sqrt[3]{-3}\cdot \sqrt[3]{-5} }

Explanation:


a)\ \sqrt[3]{-5}\cdot \sqrt[3]{3} =\sqrt[3]{-15}\\eq \sqrt[3]{15} \\\\b)\ \sqrt[3]{-15}\cdot \sqrt[3]{1} =\sqrt[3]{-15}\\eq \sqrt[3]{15}\\\\c)\ \sqrt[3]{5}\cdot \sqrt[3]{3} =\sqrt[3]{-15}\\eq \sqrt[3]{15}\\\\\large{d)\ \sqrt[3]{-3}\cdot \sqrt[3]{-5} =\sqrt[3]{15}= \sqrt[3]{15} }

User Magdala
by
5.2k points